A clinicopathological study on management of diabetic foot ulcer in tertiary care centre. (March 2023) - Rodrigues, Jude; Salelkar, Reshamarani; Rodrigues, Frazer C.S.
Abstract: Introduction: Diabetes is a disease in which the body's ability to produce or respond to the hormone insulin is impaired, resulting in abnormal metabolism of carbohydrates and elevated levels of glucose in the blood. India being the Diabetes Capital of the World has a Prevalence of 65.1 million suffering from DM of the Entire Indian Population being 1.33 billion of Worlds 6 billion people. This states that almost half of the Indian Population will sometime in their life be detected with Diabetes Almost 15–20 % of the population suffering from Diabetes are seen to have Diabetic Foot Ulcer at least once in their lifetime. It is also been noted that 10–15 % of patients suffering from Diabetic Foot Ulcer require Expert Management or Multi Disciplinary Approach. Diabetic foot ulcers have many pathogenic mechanisms, These risk factors are as follows: gender (male), duration of diabetes longer than 10 years, advanced age of patients, high Body Mass Index and other co-morbidities such as retinopathy, diabetic peripheral neuropathy, peripheral vascular disease, high glycated haemoglobin level (HbA1C), foot deformity, high plantar pressure, infections and inappropriate foot selfcare habits. Rough estimates are at about 1, 00, 000 lower limbs are amputated in India every year, of which at least seventy-five percent are neuropathic feet with secondary infections and are potentially preventable. Aims and objectives: 1) To study the Incidence of Diabetic Foot Ulcer among the Diabetics Admitted in Surgical Wards and follow up. 2) To evaluate the scoring and characteristics of Wound according to Wagner Staging and Improvement or Deterioration of Wound after Follow up of 3 months Duration. 3) To establish prognosis and Healing Status of Wounds as per the Treatment option Given and accepted by the patient. 4) To Identify the Basis of OPD level Dressings and Early Discharge versus In hospital Stay and Wound Healing. Highlights: DFUs are most common complication seen in diabetic person. The management of DFU demands multidisciplinary approach can lead to severe morbidity due development gangrene which may lead to death if not managed promptly. The poor glycaemic control was observed among majority of patients of DFU most of the ulcers were in category of Grade 3–5. One of the significant finding was OPD level dressings and early discharge showed better healing in ulcers as opposed to in hospital stay and wound healing.